2018
DOI: 10.1093/jas/sky384
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary zinc concentration and supplemental zinc source on nutrient digestibility, zinc absorption, and retention in sheep1

Abstract: The objective of this study was to assess whether supplemental Zn source or concentration would affect ruminant Zn retention and nutrient digestibility. Thirty-six weaned crossbred Polypay wethers, were sorted by BW to 3 periods and stagger started on a common diet (22 mg Zn/kg DM) for a 52-d depletion period. Day 52 BW was used to assign Zn treatments (3 lambs/treatment/ period): no supplemental Zn (CON), or supplemental Zn (40 mg Zn/d) from Zn sulfate (ING; Zinc Nacional, Monterrey, SA, Mexico), Zn methionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 30 publications
4
23
1
Order By: Relevance
“…Herbal diets can in uence the rumen microbiome, the kinetics of fermentation and the response and adaptation to anti-methanogenic compounds and diets that lead sometimes to the inconsistent e cacy of phytochemical substances [45]. Zn is also involved in a wide assortment of physiological processes; therefore, nutrient digestibility may be affected by supplemental Zn, which is incorporated into enzymes throughout the body and is critical for most metabolic processes in ruminants [46]. It is known that zinc in the nutrition of ruminants can signi cantly in uence ruminal fermentation [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbal diets can in uence the rumen microbiome, the kinetics of fermentation and the response and adaptation to anti-methanogenic compounds and diets that lead sometimes to the inconsistent e cacy of phytochemical substances [45]. Zn is also involved in a wide assortment of physiological processes; therefore, nutrient digestibility may be affected by supplemental Zn, which is incorporated into enzymes throughout the body and is critical for most metabolic processes in ruminants [46]. It is known that zinc in the nutrition of ruminants can signi cantly in uence ruminal fermentation [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that zinc retention in lambs can be similar regardless of the source of Zn or its concentration [46], the bene cial effect of zinc (i.e., antioxidant, anti-in ammatory or antiapoptotic, respectively) strongly depends on both of these factors, and too much or too little zinc in diets can lead to the opposite effect [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Carmichael et al (2018) found that increasing supplemental Zn concentrations positively impacted N retention in finishing beef steers that receive a low-fiber diet (~19% NDF). Recently, some have determined that feeding supplemental trace minerals may influence fiber digestibility ( Faulkner et al, 2017 ; Faulkner and Weiss, 2017 ; VanValin et al, 2018 ). Regardless, few studies have been conducted evaluating the relationship of fiber and Zn supplementation exceeding current recommendations ( NASEM, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Trace elements support critical functions in the body to secure the normal metabolism and homeostasis. Previously published studies on the effect of exercise are not consistent on the trace elements which deficiencies and excesses in any of them can result in the appearance of some disorders (42)(43)(44). Additionally, the blood changes in trace elements have been detected to have a role as indices of serious mood disorders such as depression in adolescents (45).…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have considered the effects of exercise on the Zn status in athletes (4, 10, 30,42,55). The early concern between exercise and Zn status was caused due to a report of a drop in the Zn blood levels in athletes as compared with nonathletes (56).…”
Section: Discussionmentioning
confidence: 99%